How macroeconomic factors impact residential real estate prices in Eastern Europe - Okunevičiūtė Neverauskienė, Laima; Linkevičius, Dominykas; Andriušaitienė, Daiva (Business, Management and Economics Engineering, 2025)
Purpose – This study examines how GDP growth, interest rates, and unemployment rates influence residential real estate prices in politically and economically stable Eastern Euro- pean countries, aiming to identify key drivers of property value changes in the region. Research methodology – The study uses multiple linear regression and Pearson correlation (r) to assess the relationship between variables and housing prices, with ARIMA (3,1,0) applied for short-term price forecasts based on cyclical time series trends. Findings – The findings show a strong correlation between macroeconomic indicators and residential real estate prices, with the key influencing factor varying by country, reflecting diverse market sensitivities and regional economic contexts. Research limitations – The research is limited to Eastern European countries with stable political and economic conditions, excluding those facing instability. Future studies could expand the analysis to include such regions to provide a more comprehensive view. Practical implications – The results provide valuable guidance for policymakers and investors in crafting strategies tailored to specific macroeconomic conditions, enhancing market predictions and stability. Originality/Value – By focusing on the underexplored residential real estate market in Eastern Europe, this study contributes novel insights into regional housing price determinants and offers a foundation for further research on macroeconomic impacts in real estate markets.